Coping skill training and family health education against anxiety in prevention substance abuse in Indonesia - Sukamti, Nita; Anna Keliat, Budi; ., Mustikasari (International Journal of Advanced Nursing Studies, 2018)
Adolescents are vulnerable to get anxiety and it can affect to substance use. Coping skill training and family health education are mental nursing intervention that is expected to overcome anxiety. The goals of the research to determine the influence of coping skill training and family health education against anxiety in Junior High School. The research design is quasi-experimental pre-posttest with control group and 87 students in Junior High School was chosen by using purposive sampling technique then continued with cluster random sampling. Respondents were divided into 2 groups. Group 1 get nursing intervention and group 2 get nursing intervention, coping skills training, and family health education. The results showed decrease of anxiety that not significant after nursing intervention (p value > 0.05), and significantly decrease of anxiety after the coping skill training and family health education (p value < 0,05). Coping skill training and family health education is recommended to decrease anxiety in adolescent.Â Â